ANALISIS PENGARUH PEMILIHAN METODE AKUNTANSI TERHADAP TINGKAT UNDERPRICING SAHAM PERDANA - Susi Dwimulyani; Edwin Arius (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2006)
This paper is want to study and check the influence of accounting methods choices to underpricing level of Initial Public Offering (IPO). Sample data are used 64 companies Initial Public Offering lists in Jakarta Stocks Exchange of the year 2000-2003. Accountingmethod comprises fixed asset accounting depreciation method, accounting inventory method and also signal of ownership. The analysis of data using Independent Sample T test and Single Regression.The result of this research shows that examination score bigger than 0,05 by using independent sample T test and Single Regression with significant level 0.05. If the result of examination show smaller than significant level hypothesis can be accepted, if level significant bigger than 0.05, hence hypothesis refused. Hypothesis 1 and 2 had thesignificant level bigger than 0.05. So in this research hypothesis 1 and 2 are refused, because no different significant underpricing means was caused by the choices of accounting methods. Hypothesis 3 had the significant level smaller than 0.05. So in thisresearch hypothesis 3 is accepted, because there is significant influence from signal of ownership to underpricing level.